Infant Botulism and Honey - Malcolm T. Sanford; Eddie Atkinson; Jeanette Klopchin; Jamie Ellis (EDIS)
Since honey is a potential and avoidable source of Clostridium botulinum spores, the Center for Disease Control and Prevention, the American Academy of Pediatricsm and the National Honey Board recommend that honey not be given to infants younger than 12 months of age. Honey should not be added to water, food, or formula fed to infants under 12 months of age. This 2-page fact sheet was written by Malcolm T. Sanford, Eddie Atkinson, Jeanette Klopchin, and Jamie Ellis, and published by the UF Department of Entomology and Nematology, June 2013.